A framework of analysing virtual transfer pricing mechanisms in global supply chain. (2018) - Liao, Kun; Ke, Ke; Wang, Yan
Supply chain is a network of financial flow while contract is a primary way of recognising and distributing profits between buyer and supplier in a supply chain. Virtual transfer pricing defined in this study is the mechanism of using contract bundles within a global supply chain to maximise profit. We propose three virtual transfer pricing models. The models are articulated with mathematical presentations for clarity. This is one of the first studies to identify basic components of virtual transfer pricing which have significant implications for firms in global supply chains as well as governmental tax agencies all over the world.